Lingual Thyroid Gland: Diagnosis and Treatment (International Journal of Medical and Surgical Sciences, 2016)
The presence of ectopic thyroid gland is a rare entity. The lingual thyroid is the most frequent ectopy, predominating in women. This glandular tissue is capable of suffering all the pathologies that can affect the normotopic gland, being able to be symptomatic or asymptomatic. We present a case of lingual thyroid in a previously thyroidectomized patient who consulted for dyspnea and dysphagia in the Head and Neck Surgery Unit of the Otolaryngology Service of the Central Hospital of the Institute of Social Prevision, Asuncion, Paraguay. The patient received hormone replacement therapy, showing normal functional examination. Semiology allowed to observe a bulging of the base of the tongue. The fibroscopy showed a tongue-based tumor about 3 cm in diameter, which could be correctly evaluated with computed tomography. Suspicion of a lingual thyroid was performed with a scintigram demonstrating uptake in the oral cavity floor. Tumor excision was performed through a suprahyoid pharyngotomy, following a prophylactic tracheostomy. The Pathologic Anatomy report confirmed the diagnosis of ectopic colloid goitre.